A note on the use of dolphins as bait in the artisanal fisheries off Bahía Solano, Chocó, Colombia - Avila , Isabel Cristina; Garcia , Carolina; Bastidas , Juan Carlos (J. Cetacean Res. Manage., 2023)
Dolphin hunting for fishing bait in Bahía Solano, Chocó, Colombia, was evaluated during eight months, between July 2005 and April 2006. Interviews were conducted with 122 fishermen (18.2% of the registered fishermen in the zone), who cover at most 890km2 when fishing (approximately 2.3% of the Pacific Territorial Sea of Colombia), and data obtained from landings at a fishing company. Only fishermen using longlines (37.3%) confirmed using dolphins as bait. It was not possible to obtain additional information about date, specific location or dolphin species, but the most probable captured species were common bottlenose dolphin and pantropical spotted dolphin. Nine dolphins were killed during the study period (1.1 dolphins/month) and extrapolating these numbers to all fishermen using longlines in the region (250), 24 dolphins might have been taken during the study period (3 dolphins/month). Fish species caught using dolphin bait include Pacific bearded brotula, groupers and smooth-hound.